Advanced Technologies to Smart Grid Systems: Challenges and Demands - Remah Bani Younisse; Mouhammd Alkasassbeh; Amjad Aldweesh (IEEE Access)
Smart grid systems are designed to allow bidirectional communication between smart meters’ side and control systems on the utility side. They are essential to incorporate green energy resources into grid systems. This incorporation allows for optimized green energy integration in grid systems. Thus, minimizing reliance on non-clean energy resources and limiting harmful gas emissions in the environment will ultimately contribute to a more sustainable and eco-friendly energy infrastructure. They also open the door widely for smart city technologies to become a reality. Nevertheless, there are many challenges facing the transformation from traditional to smart grid systems. Many of these challenges are related to security and resiliency problems. This work reviews research papers incorporating advanced technologies to enhance smart grid systems. This work explores five scopes in smart grid systems: 5G, fog computing, multi-agent reinforcement learning, heartbeat, and self-healing technologies. A comprehensive discussion is presented on every scope, focusing on their role in smart grid systems, especially resiliency and security. The reviewed works reveal the strengths of these technologies and the advantages achieved when each technology is applied in smart grid systems. Meanwhile, this review stresses the need to create a comprehensive framework for smart grid systems that integrates multiple advanced technologies. The framework should use emerging and advanced technologies to guarantee efficiency, security, and resiliency.